If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -4m + -2 = -16 Reorder the terms: 6 + -2 + -4m = -16 Combine like terms: 6 + -2 = 4 4 + -4m = -16 Solving 4 + -4m = -16 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -4m = -16 + -4 Combine like terms: 4 + -4 = 0 0 + -4m = -16 + -4 -4m = -16 + -4 Combine like terms: -16 + -4 = -20 -4m = -20 Divide each side by '-4'. m = 5 Simplifying m = 5
| 6-4m-2=16 | | 3x-44=2x+20 | | 3-a=2a-9 | | 5+4k+1=-2 | | x^2+y^2-10x-18y+81=0 | | 7n^2-4n-17=0 | | 7+2y=-13 | | 3x+33=84 | | c=2(3.14)32 | | Y+5=-6(x-1) | | 5*3-8/2*3 | | 4n-5=n+25 | | -2(b+5)=12+b | | -7x+5(-4x+17)=-185 | | 8b+16-2b=4b | | -5x+5=19+2x | | m-7=3m-1 | | 175=123-y | | 12mn-4m^2-9n^2=0 | | -3+-7g+7+-7= | | x^4-x^3-x^2-5x-2=0 | | 243.80=.65y+.75x | | -160=7x-3(6x+13) | | 4m-3=5m-9 | | 7x+-19y=-17 | | y=6000x | | 3y+9=12y+13 | | -147=-7x+7(5x+3) | | 4(X-6)-1=31 | | 2u-7=-11 | | 2m+15=-27 | | -4K-3=-7 |